2014
DOI: 10.1111/febs.12834
|View full text |Cite
|
Sign up to set email alerts
|

Role of dynamin and clathrin in the cellular trafficking of flotillins

Abstract: Flotillin-1 and flotillin-2 are highly conserved, membrane-microdomainassociated proteins that have been shown to be involved in signal transduction, membrane trafficking and cell adhesion. Upon growth factor stimulation, flotillins are tyrosine phosphorylated and become endocytosed from the plasma membrane into endosomes from which they are recycled back to the plasma membrane. Although a role for flotillin-1 in the endocytosis of certain cargo proteins has been suggested, it is not known how the growthfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 90 publications
(168 reference statements)
1
19
0
Order By: Relevance
“…Although of potential interest, it is not known whether this flotillin-dependent cadherin recycling mechanism exists in other cell types. It is noteworthy that A431 cells overexpress EGFR and this could affect endocytosis and recycling of cadherin and flotillin (Bryant et al, 2007;Meister et al, 2014). Moreover, we never observed such a mechanism in the cell lines we tested.…”
Section: Flotillin-dependent Regulation Of Cadherin Recyclingmentioning
confidence: 68%
“…Although of potential interest, it is not known whether this flotillin-dependent cadherin recycling mechanism exists in other cell types. It is noteworthy that A431 cells overexpress EGFR and this could affect endocytosis and recycling of cadherin and flotillin (Bryant et al, 2007;Meister et al, 2014). Moreover, we never observed such a mechanism in the cell lines we tested.…”
Section: Flotillin-dependent Regulation Of Cadherin Recyclingmentioning
confidence: 68%
“…Flotillin redistribution from the plasma membrane to late endosomes is induced also by incubation with EGF [57,58]. In HeLa cells, this effect involves dynamin [59]. It has been suggested that Fyn-dependent phosphorylation of flotillin 1 (Y160) and flotillin 2 (Y163) induces their endocytosis.…”
Section: Flotillinsmentioning
confidence: 99%
“…The lipid raft is also a major source of Ab generation, and the plasma membranes of DNM2-negative neuronal cells have been found with an increase in the concentration of the lipid raft. An increased amount of flotillin-1, a marker of lipid raft, was found to be in the plasma membrane of DNM2-negative neuronal cells, confirming the increased presence of lipid raft (Meister et al, 2014). DNM1 knockout mice show reduced levels of secreted and intracellular levels of Ab in cell cultures.…”
Section: Dynamin In Admentioning
confidence: 62%